Sufficiency as relations of enoughness - Eric Hartmann (Sustainable Development, 2024)
Abstract An expanding body of literature discusses the importance of sufficiency for sustainable development. However, conceptual vagueness stands in the way of the practical application of sufficiency as a sustainability strategy. The main contribution of this paper is the introduction of the concept of relations of enoughness , building on the general notion of `enough', which is prevalent in sufficiency literature. Relations of enoughness will be explained based on the widespread use of sufficiency advocating for changes and reductions of individual consumption with the goal to reduce environmental impacts such as carbon dioxide emissions. Diverse uses and understandings of sufficiency can be united in a shared structure of `enough/too much/too little of X regarding Y'. Relations of enoughness can be connected to sustainability by expanding them into chains of enoughness , which serve as a conceptual foundation for the sustainable consumption corridor approach. Finally, the premises of sufficiency and potential for further research are discussed.
Keywords: 330; ecological limits; enough; human needs; relation; sufficiency; sustainability strategy; sustainable consumption